أثر التلقيح الصناعي على جنسية المولود من أب أردني واقع وضرورة ضبط - الحجايا، نور حمد (جامعة الكويت - مجلس النشر العلمي, 2019)
يعد التلقيح الصناعي من حيث المبدأ وسيلة مساعدة طبية تسعى إلى تحقيق الإنجاب الصناعي لمن لا يستطيعون الإنجاب الطبيعي. وقد انتشرت هذه الوسيلة بحيث إنها لم تعد وسيلة خاصة لمساعدة من لا يستطيعون الإنجاب الطبيعي بل استخدمت من قبل الأشخاص القادرين على الإنجاب الطبيعي بهدف الحصول على جنس معين من المواليد، أو للحصول على عدد معين من المواليد. ولأن اللجوء إلى عملية التلقيح يثير التساؤل حول مشروعية عملية التلقيح ذاتها، ومن ثم الشك بنسب المولود المنبثق عن تلك العملية لاحتمال أن تلقح بويضة الزوجة بحيوان منوي لرجل أجنبي، أو لاحتمال أن تجرى عملية التلقيح بعد وفاة الزوج أو بعد الطلاق، ناقشت الدارسة أثر عملية التلقيح على جنسية المولود من أب أردني التي تعتمد على ثبوت النسب شرعا. ولقد تناولت في هذه الدراسة أثر التلقيح الصناعي أثناء الحياة الزوجية على جنسية المولود، وأثره بعد انتهاء العلاقة الزوجية على تلك الجنسية، ومن ثم تم وضع ضوابط لتحقيق التوازن بين حق الأبوين في الإنجاب، وحق الدولة في منح جنسيتها لأبناء الأردني دون ارتكاب غش على قواعد النسب. وفي خاتمة هذه الدراسة خلصنا إلى العديد من النتائج والتوصيات.
Artificial insemination is considered a technique that can help treat certain kinds of infertility in principle. It is seeking a medical help to achieve childbearing, and ideally, it makes pregnancy possible where it was not before (Intrauterine insemination). It is also used by people who are capable of natural reproduction in order to obtain certain genus of births or to obtain a certain number of births. The recourse to the process of artificial insemination raises a question about the legality of the insemination process itself, And then it raises the doubt of the descent born emanating from that process for the possibility that the fertilized ovum by a sperm from a foreign man or the possibility that the process of insemination takes place after the death of a spouse or after a divorce. The study discusses the impact of the insemination on the child’s nationality of a Jordanian father and how to prove the biological father. The study also discusses the impact of the artificial insemination on the nationality of the child during the marital relationship, and its impact after the end of the marital relationship to that nationality of the child. The study also suggested standards to achieve a balance between the right of parents to reproduction and the right of the state to grant citizenship to the child of a Jordanian father without committing fraud on the descent rules. In conclusion, this study delivered findings and recommendations.
Keywords: الفقة الإسلامي -- التشريع الإسلامي -- التلقيح الصناعي -- المولود -- الأب -- الأم -- الأحكام الشرعية -- مستخلصات الأبحاث